Social Entrepreneurship and Social Innovation in Aging - Jorge Felix; Andrzej Klimczuk (Encyclopedia of Gerontology and Population Aging, 2020)
Social entrepreneurship is usually understood as an economic activity which focuses at social values, goals, and investments that generates surpluses for social entrepreneurs as individuals, groups, and startups who are working for the benefit of communities, instead of strictly focusing mainly at the financial profit, economic values, and the benefit generated for shareholders or owners. Social entrepreneurship combines the production of goods, services, and knowledge in order to achieve both social and economic goals and allow for solidarity building. From a broader perspective, entities that are focused on social entrepreneurship are identified as parts of the social and solidarity economy. These are, for example, social enterprises, cooperatives, mutual organizations, self-help groups, charities, unions, fair trade companies, community enterprises, and time banks. Social innovation is a key element of social entrepreneurship. Social innovation is usually understood as new strategies, concepts, products, services, and organizational forms that allow for the satisfaction of needs. Such innovations are created in particular in the contact areas of various sectors of the social system. For example, these are spaces between the public sector, the private sector, and civil society. These innovations not only allow the solving of problems but also extend possibilities for public action.
Keywords: J14; J18; O35; 300; Aging and innovation; Aging and entrepreneurship